Subaru Near-Infrared Imaging Polarimetry of Misaligned Disks Around the Sr 24 Hierarchical Triple System - Perez-Marquez, S (Institute of Physics Publishing, 2020)
The SR 24 multistar system hosts both circumprimary and circumsecondary disks, which are strongly misaligned with each other. The circumsecondary disk is circumbinary in nature. Interestingly, both disks are interacting, and they possibly rotate in opposite directions. To investigate the nature of this unique twin disk system, we present 0.″1 resolution near-infrared polarized intensity images of the circumstellar structures around SR 24, obtained with HiCIAO mounted on the Subaru 8.2 m telescope. Both the circumprimary disk and the circumsecondary disk are resolved and have elongated features. While the position angle of the major axis and radius of the near-IR (NIR) polarization disk around SR 24S are 55° and 137 au, respectively, those around SR 24N are 110° and 34 au, respectively. With regard to overall morphology, the circumprimary disk around SR 24S shows strong asymmetry, whereas the circumsecondary disk around SR 24N shows relatively strong symmetry. Our NIR observations confirm the previous claim that the circumprimary and circumsecondary disks are misaligned from each other. Both the circumprimary and circumsecondary disks show similar structures in 12CO observations in terms of its size and elongation direction. This consistency is because both NIR and 12CO are tracing surface layers of the flared disks. As the radius of the polarization disk around SR 24N is roughly consistent with the size of the outer Roche lobe, it is natural to interpret the polarization disk around SR 24N as a circumbinary disk surrounding the SR 24Nb-Nc system. © 2019. The American Astronomical Society.